Pemerintahan Desa dan Urgensi Pemeliharaan Tata Kelola Sebagai Wujud Pembangunan Daerah Melalui Pembaharuan Hukum - Muhammad Mas Davit Herman Rudiyansah (Bestuurskunde: Journal of Governmental Studies, 2025)
The village is part of the regional government that can help support the overall economy of the territorial region. The existence of village regulations is intended as a mutual benefit that promotes village efficiency. Previous research has examined the urgency of revising the Law, so the focus gap of this study lies in reviewing the enactment of Law No. 3 of 2024, which is the second amendment to Law No. 6 of 2014 concerning Villages, as an effort to optimize village development. Through a review using empirical legal methods, this study finds that the enactment of Law No. 3 of 2024 concerning Villages is one of the steps taken by the central government to optimize village governance. Law No. 6 of 2014 concerning Villages is considered inadequate in accommodating the need for legal certainty at the village level. Therefore, the presence of Law No. 3 of 2024 is expected to provide answers to unresolved issues that were not sufficiently addressed by Law No. 6 of 2014.